Coaching, not monitoring? Insights from a school accountability reform in Pakistan - Karachiwalla, Naureen; Kosec, Katrina; Asad, Saher; Habib, Masooma; Leaver, Clare; ur Rehman, Attique (International Food Policy Research Institute, 2020)
We evaluate a pilot reform of the promotion system for teachers and head teachers in Khyber Pakhtunkhwa province, Pakistan, that was implemented as a randomized controlled trial during the 2017-2018 school year. District officials were asked to visit treatment schools to monitor educator behavior and student performance passively. Educators in treatment schools were told that their relative performance on these measures would determine their promotion speed. District officials were asked to continue with 'business as usual' visits in control schools, during which they often coached educators. We find null treatment effects for all pre-registered student and educator outcomes. In-class teaching practices improved from baseline to endline, but these sizeable changes were similar in magnitude in all schools. Videos of inspection visits and follow-up interviews reveal that district officials coached teachers on these practices in all schools, indicating that they struggled to adapt their 'mental model' to the new accountability regime.